Concordance patterns in zooplankton assemblages in the UHE - Luís Eduardo Magalhães reservoir in the Mid-Tocantins river, Tocantins State, Brazil - doi: 10.4025/actascibiolsci.v33i2.7336 - Bessa, Gisele Fernandes (2011)
The goal of this study was to evaluate the concordance amongst three zooplankton groups (Rotifera, Cladocera, and Copepoda) and between the zooplankton groups and the environmental variables in the Luis Eduardo Magalhães reservoir, in the Mid-Tocantins River, Tocantins State, Brazil. Concordance patterns were found in relation to environmental variables, cladocerans, and rotifers, although values were relatively low. These results indicate that one should be cautious about the use of indicative taxonomic groups to detect environmental changes, where divergent results annul extrapolation possibilities and indicate the existence of distinct environmental factors controlling different groups.